Inflation and Life Expectancy in Nigeria: A Causal Analysis: Array - Lawal, Nurudeen Abiodun; Osinusi, Kunle Bankole; Bisiriyu, Sodiq Olaide (Acta Universitatis Danubius. Œconomica, 2021)
This study focused on the examination of inflation and life expectancy in Nigeria using causal analysis from 1980 to 2019. The study acknowledges literature on the determinants of life expectancy and overview of life expectancy in Nigeria over the years as well as the overview in some selected developed and Sub-Saharan Africa countries. The study gathered secondary data from World Bank World Development Indicators Dataset for empirical analysis by adopting ADF unit root test, VAR autoregressive lag order and Granger Causality test. The result revealed that all the incorporated data are stationary justifying their inclusion for analysis. The Granger causality result affirmed no causality between life expectancy and inflation rate in Nigeria over the years of analysis while there is uni-directional causality in the other variable (exchange rate) and life expectancy over the period of analysis in Nigeria. This means inflationary trend in Nigeria was not significant in influencing life expectancy in Nigeria while exchange rate does. The study thus recommends that government agencies and monetary authorities in Nigeria should carefully provide frameworks that will ensure stability in exchange rate having known it’s significance on life expectancy while health policy maker, practitioners, government health ministry should develop plans and means of increasing life expectancy rate in Nigeria as the figure stood low among some other Africa countries and the world as a whole.